Acetoxy Chavicol Acetate (ACA) Concentration and Cytotoxic Activity of Alpinia galanga Extract on HeLa, MCF7 and T47D Cancer Cell Lines - Andi Suhendi; Erindyah Retno Wikantyasning; Gunawan Setyadi; Arifah Sri Wahyuni; Muhammad Da'i (Indonesian Journal of Cancer Chemoprevention, 2017)
Due to severe side effect and non-specific chemotherapeutic agent, screening and discovery for cancer therapy are still working, especially from natural resources. Traditionally, people used herbal medicine either to prevent or cure diseases. One of herbal that commonly used in Indonesia is Alpinia galangal. Previous study stated that active compound is acetoxy chavicol acetate (ACA) and active as anticancer. This research aimed to determine ACA concentration and cytotoxic activity of Alpinia galanga extract (AGE) from three local markets on HeLa, MCF7 and T47D cell lines. The galangal used from three local markets namely Pasar Legi Surakarta, Beringharjo Yogyakarta, and Wonogiri. The extraction was performed by maceration using 96% ethanol as solvent. ACA quantitation using UV spectrophotometer at λ = 208.5 nm. Samples were prepared by liquid-liquid extraction using an ethyl acetate. Cytotoxic activities were performed by MTT assay. The result showed that the concentration of ACA of AGE from the three local markets were 3.798; 0.035; and 0.009 % w/w, respectively. Cytotoxic activity, describes as IC50 value, on HeLa cell line of AGE from three local markets, in order were 13.26; 36.32 and > 100 µg/ mL. Meanwhile, AGE from Pasar Legi on MCF7 and T47D cell lines have IC50 value of 15.80; 12.50 µg/ mL, respectively. In contrast, two other samples have IC50 values of greater than 100 µg/ mL. The highest activity was from the highest concentration of ACA on the samples.Key words: Alpinia galanga, HeLa, T47D, MCF7 and Acetoxy chavicol acetate